P1108FLUID DYNAMIC ASSESSMENT OF THERANOVA DIALYZER THROUGH CT IMAGING TECHNIQUE. (6th June 2020) - Lorenzin, Anna; Golino, Gianlorenzo; Godi, Llaria; De Cal, Massimo; Ronco, Claudio
Abstract: Background and Aims: Inadequate removal of molecules between 5and50KDa, due to their restriction in diffusibility, may cause long-term complication in chronic hemodialysis patients. Medium Cut-off(MCO) is a new class of membranes with enhanced sieving properties and negligible albumin loss, thanks to its high molecular weight(MW) retention onset and MW cut-off value lower than albumin MW. MCO membrane used in HD allows to perform expanded hemodialysis (HDx), a technique based on high internal filtration(IF). Our previous study quantified the IF of Theranova dialyzer leveraging a nuclear imaging technique. In order to characterize the local distribution of the IF, an in vitro study assessing the fluid dynamics inside Theranova dialyzer was conducted through CT imaging technique. Method: Dialyzers Theranova 400 and 500(Baxter, Deerfield, USA) were placed in vertical position in the CT gantry. Blood and dialysate were circulated in countercurrent at 300ml/min and 500 ml/min, respectively. The two compartments were analyzed separately, injecting the dye solution, for both filters. Longitudinal sections, 0.5cm thick, were recorded for 60seconds. Results: In blood compartment, dye solution immediately after its entrance in the dialyzer demonstrates homogeneous progression, while different velocity profiles were observed among the fibers proceeding to the outlet port (Fig b). In dialysate compartment, dye solution is distributed in the periphery first (Fig d), then seeps in the fibers bundle and reaches the complete compartment filling. Conclusion: The homogeneous dye profile immediately after its entrance in blood compartment demonstrated a good design of the inlet port; the optimal dye distribution reached in both blood and dialysate compartments ensure that IF phenomenon is equally achieved in both central and peripheral regions of the dialyzer.